Effect of ionic strength and mixing ratio on complex coacervation of soy protein isolate/Flammulina velutipes polysaccharide - Junmiao Zhang; Hengjun Du; Ning Ma; Lei Zhong; Gaoxing Ma; Fei Pei; Hui Chen; Qiuhui Hu (Food Science and Human Wellness)
Soy protein isolate (SPI) is a commercial protein with balanced amino acids, while the poor solubility impedes its use in traditional foods. To overcome the problem, the complex coacervation of SPI/Flammulina velutipes polysaccharide (FVP) were investigated. Initial results revealed that the suitable amounts of FVP contributed to reducing the turbidity of SPI solution. Under electrostatic interaction, the formation of SPI/FVP coacervates were spontaneous and went through a nucleation and growth process. Low salt concentration (CNaCl = 10, 50 mmol/L) led to an increase in the critical pH values (pHc, pHφ1) while the critical pH values decreased when CNaCl ≥ 100 mmol/L. The concentration of NaCl ions increased the content of α-helix. With the increase of FVP, the critical pH values decreased and the content of β-sheet increased through electrostatic interaction. At SPI/FVP ratio of 10:1 and 15:1, the complex coacervation of SPI/FVP were saturated, and the coacervates had the same storage modulus value. SPI/FVP coacervates exhibited solid-like properties and presented the strongest storage modulus at CNaCl = 50 mmol/L. The optimal pH, SPI/FVP ratio and NaCl concentration of complex coacervation were collected, and the coacervates demonstrated a valuable application potential to protect and deliver bioactives and food ingredients.